Does activation of oxytocinergic reward circuits postpone the decline of the aging brain? - Buemann, Benjamin (Frontiers in Psychology, 2023)
Oxytocin facilitates reproduction both by physiological and behavioral mechanisms. Oxytocinergic neurons emerging from the hypothalamus release oxytocin from the pituitary gland to the blood by axonal discharge. This regulates reproductive organs but at the same time, oxytocin is secreted into neighboring areas of the hypothalamus from the dendrites of these neurons. Here the oxytocin acts by autocrine and paracrine mechanisms to influence other neuroendocrine systems. Furthermore, oxytocinergic neurons project to many different locations in the brain where it affects sensory processing, affective functions, and reward. Additional to its regulatory role, significant antiinflammatory, restoring, and tranquilizing effects of oxytocin have been reported from many in-vivo and in-vitro studies. The oxytocin system may therefore have the capacity to alleviate detrimental physiological-and mental stress reactions both peripherally and centrally. Thus, high levels of endogenous oxytocin may counteract inadequate inflammation and malfunctioning of neurons and supportive cells in the brain. A persistent low-grade inflammation increasing with age -referred to as inflammagingmay lead to a cognitive decline but may also predispose to neurodegenerative diseases such as Alzheimers and Parkinson. Furthermore, animal experiments have documented the importance of preserving immune-and stem cell functions in the hypothalamus to impede age-related destructive processes in the body. It is argued in this article that sexual activity -by its stimulating impact on the oxytocinergic activity in many regions of the brainhas the capacity to delay the onset of age-related cerebral decay. This may also postpone frailty and age-associated diseases in the body. Furthermore, suggestions are given how the neuroplastic properties of oxytocin may be utilized to enhance sexual reward by learning processes in order further to reinforce the release of oxytocin. It may therefore be profitable to raise the consciousness about the potential health benefits of sexual activity particularly among the seniors.